Effect of Harvest on a Brown Bear Population in Alaska. Issue 5 (11th March 2020) - Brockman, Chris; Guttery, Michael R.; Dale, Bruce W.; Schwanke, Rebecca A.; Tobey, Robert W.; Koons, David N.
ABSTRACT: There is a long and contentious history of brown bear ( Ursus arctos ) harvest management in Alaska, USA, the state that hosts the largest brown bear population in North America. In the mid‐1990s, the Alaska Board of Game set the population objective for brown bears in Game Management Unit 13 A, located in interior southcentral Alaska, to be reduced by 50% to improve survival of moose ( Alces alces ) calves. The Board began further liberalizing brown bear harvest regulations for the unit beginning in regulatory year 1995, though adult females and their dependent offspring (i.e., cubs <2 yrs old) were protected. To evaluate progress toward this abundance objective, we captured and collared bears between 2006 and 2011 and conducted a capture‐mark‐resight density survey during summer 2011 for comparison to a similar baseline survey conducted in 1998. We report the results of the density survey and vital rates estimated from resight histories of collared bears and harvest information spanning from 1985 (10 years before establishment of the population objective) to 2012. There was a 25–40% reduction in abundance between 1998 and 2011. Population growth rates derived from density estimates and a matrix population projection model indicated that the population declined by 2.3–4.2% annually. We estimated harvest rates to be 8–15% annually, but harvest composition data indicated no changes in skull size, age distribution, or overall sex ratio. There was evidence of an increase in the proportion of older females in the harvest. Demographic analysis indicated high reproductive output and recruitment, potentially indicating a density‐dependent compensatory response to reduced population size. Despite 13 years of harvest rates in excess of what had previously been considered to be sustainable for this population, the objective of reducing bear abundance by 50% had not been achieved as of 2011. The protection of females and dependent offspring in our study population appears to be a sufficient safeguard against a precipitous population decline while still permitting progress toward the population objective through high harvest on other segments of the population. © 2020 The Wildlife Society. Abstract : We report harvest records, density estimates, and survival and reproductive estimates for a brown bear population in Alaska being managed for a 50% abundance reduction. After 16 years of liberal harvest regulations, the population reduction objective had not been met, likely because of regulatory protection of reproductive females and their dependent young.